Comprehensive analysis of epigenomics and transcriptome data to identify potential target genes associated with obesity - Wu, Peili; Guo, Lei; Li, Xuelin; Du, Yuejun; Lin, Xiaochun; Ma, Xiaoqin; Lin, Yingbei; Wen, Churan; Yang, Chuyi; Liu, Nannan; Feng, Qijian; Xue, Yaoming; et al. (Frontiers in Genetics, 2022)
DNA methylation is closely related to the occurrence and development of many diseases, but its researches in obesity are still limited. This study was aimed at finding potential differentially methylated genes associated with the occurrence and development of obesity. In this study, by combining methylation and transcriptome analysis, we identified the key genes in adipose tissue that may affect the occurrence and development of obesity, and revealed the possible molecular mechanisms involved in pathomechanism of obesity. We first screened 14 methylation related differential genes and verified their expression in adipose tissue by qPCR. Seven genes with the same expression pattern were identified as key genes, namely CCRL2, CHST1, GPT, LGALS12, PC, SLC4A4, and TTC36. Secondly, the immune microenvironment of adipose tissue was quantified by CIBERSORT, and we found that the content of macrophages M0 and T follicular helper cells in adipose tissue were significantly increased and decreased respectively in obese group. And the relationship between key genes and immune microenvironment was analyzed as well. Additionally, the metabolic pathway activity of each sample was calculated based on the ssGSEA algorithm and the key gene-metabolic network was constructed. Moreover, we also performed CMAP analysis based on the differential genes in adipose tissue to screened out potential drugs that are effective in the treatment of obesity. In conclusion, we identified seven methylation-related key genes that may closely related to the pathogenesis of obesity, and explored the potential mechanism of their influence on obesity. This study provides novel insights into the molecular mechanism and management of obesity.